Lithium metal battery and method for producing lithium metal battery
By using a first polymer electrolyte derived from single-ion conductive monomer and crosslinked monomer in a lithium metal battery, the side reaction problem caused by electrolyte oxidation at high voltage is solved, and the battery performance is improved and the life of the battery is extended.
Patent Information
- Application Number
- CN202380062228.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-26
- Filing Date
- 2023-08-24
- Publication Date
- 2025-04-08
AI Technical Summary
The side reaction of lithium metal batteries at high voltages is caused by the oxidation of electrolytes, which leads to rough surface of the lithium metal negative electrode and growth of lithium dendrites, causing a short circuit between the negative electrode and the positive electrode, deteriorating the battery performance.
Using an electrolyte including a first polymer electrolyte, the first polymer electrolyte is composed of a single ion conductive monomer and a crosslinked monomer, for forming a new structure that prevents deterioration of the positive electrode electrolyte and inhibits the growth of the negative electrode lithium dendrites.
It effectively prevents the deterioration of the positive electrode electrolyte and the side reaction of the lithium metal negative electrode, improves the circulation characteristics of the lithium metal battery, and extends the battery life.
Smart Images

Figure CN119790517A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a negative electrode for a lithium metal battery, a lithium metal battery including the same, and a method for manufacturing the negative electrode for a lithium metal battery. Background Art
[0002] In the lithium batteries currently on the market, carbon negative electrode active materials such as graphite are mainly used. Carbon negative electrode active materials do not change in volume during charging and discharging, so lithium batteries have high stability. The theoretical capacitance of graphite is 372mAh / g.
[0003] Lithium metal can be used as a negative electrode active material. The theoretical capacitance of lithium metal is 3860 mAh / g. Lithium metal causes a short circuit with the positive electrode due to a side reaction with the electrolyte during charging and discharging, thereby deteriorating the life characteristics of lithium metal batteries. Summary of the invention
[0004] Technical issues A lithium metal battery includes a high voltage positive electrode and a lithium metal negative electrode. Since the high voltage positive electrode operates at a high voltage of 3.5V or higher (or 4.0V or higher), the organic solvent included in the electrolyte is oxidized at a high voltage, thereby causing a side reaction between the electrolyte and the positive electrode, resulting in the degradation of the lithium metal battery. When the lithium metal negative electrode is charged and discharged, a lithium metal layer is plated or dissolved between the electrolyte and the lithium metal negative electrode. As the charging and discharging of the lithium metal battery is repeated, the lithium metal layer includes impurities remaining in the electrode due to side reactions with the electrolyte, decomposition products of the electrolyte, and the like. The surface of the lithium metal layer including these impurities becomes rough and hard. Lithium dendrites are plated on the lithium metal layer having a rough and hard surface. Lithium dendrites continue to grow during the charging and discharging process, resulting in a short circuit between the negative electrode and the positive electrode. As a result, the lithium metal battery deteriorates. Therefore, it is necessary to prevent side reactions at the high voltage positive electrode of the lithium metal battery and inhibit the growth of lithium dendrites at the negative electrode.
[0005] One aspect is to provide a lithium metal battery including an electrolyte of a novel structure that prevents side reactions at a high voltage positive electrode of the lithium metal battery and suppresses the growth of lithium dendrites at a negative electrode.
[0006] Another aspect is to provide a method for making a lithium metal battery.
[0007] Technical Solution According to an embodiment, there is provided a lithium metal battery, the lithium metal battery comprising: a positive electrode, a negative electrode, and an electrolyte disposed between the positive electrode and the negative electrode, Wherein, the negative electrode comprises lithium metal, The electrolyte includes a positive electrode electrolyte disposed adjacent to the positive electrode and a negative electrode electrolyte disposed between the positive electrode electrolyte and the negative electrode. The positive electrode electrolyte includes a first polymer electrolyte, and the first polymer electrolyte includes a first polymer, and The first polymer includes a first repeating unit derived from a first single ion conductive monomer and a second repeating unit derived from a first cross-linking monomer having a plurality of reactive functional groups.
[0008] According to another embodiment, there is provided a method for manufacturing a lithium metal battery, the method comprising: preparing a composition for forming a positive electrode electrolyte; preparing a composition for forming a negative electrode electrolyte; applying a composition for forming a negative electrode electrolyte onto a lithium metal negative electrode; cross-linking the applied composition for forming a negative electrode electrolyte to prepare a lithium metal negative electrode coated with the negative electrode electrolyte; stacking a lithium metal negative electrode coated with a negative electrode electrolyte, a porous membrane, and a positive electrode to prepare an assembly; injecting a composition for forming a positive electrode electrolyte into the assembly; and cross-linking the injected composition for forming a positive electrode electrolyte to prepare a lithium metal battery including the positive electrode electrolyte, The lithium metal battery includes a positive electrode, a negative electrode and an electrolyte disposed between the positive electrode and the negative electrode. The positive electrode electrolyte includes a first polymer electrolyte, and the first polymer electrolyte includes a first polymer, and The first polymer includes a first repeating unit derived from a first single ion conductive monomer and a second repeating unit derived from a first cross-linking monomer having a plurality of reactive functional groups.
[0009] Beneficial Effects According to one aspect, a lithium metal battery having an electrolyte with a novel structure that prevents degradation of a positive electrode electrolyte, prevents side reactions of a lithium metal negative electrode, and improves cycle characteristics can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 is a schematic cross-sectional view of a lithium metal battery according to example embodiments.
[0011] Figure 2a is a scanning electron microscope image of the surface of the lithium metal negative electrode coated with the negative electrode electrolyte prepared in Preparation Example 2.
[0012] Figure 2b is a scanning electron microscope image of the surface of the lithium metal negative electrode prepared in Comparative Preparation Example 3.
[0013] Figure 3is a graph showing the electrochemical stabilities of the positive electrode electrolytes prepared in Preparation Example 1 and Comparative Preparation Example 1.
[0014] Figure 4 is a scanning electron microscope image of a cross section of the negative electrode of the lithium metal battery manufactured in Evaluation Example 4 after charging.
[0015] Figure 5 is a graph showing the results of measuring the life characteristics of the lithium metal batteries manufactured in Example 1 and Comparative Examples 1 and 2.
[0016] Figure 6 is a schematic diagram of a lithium metal battery according to example embodiments.
[0017] Figure 7 is a schematic diagram of a lithium metal battery according to example embodiments.
[0018] Figure 8 is a schematic diagram of a lithium metal battery according to example embodiments. DETAILED DESCRIPTION
[0019] The inventive concept described below may be subjected to various changes and may have various embodiments, and specific embodiments are shown in the drawings and described in detail. However, this is not intended to limit the inventive concept to specific embodiments, and should be understood to include all changes, equivalents or substitutes included in the technical scope of the inventive concept.
[0020] The terms used below are only used to describe specific embodiments and are not intended to limit the inventive concept. Unless the context clearly provides otherwise, singular expressions include plural expressions. Hereinafter, terms such as "including" or "having" are intended to indicate the presence of features, numbers, steps, operations, components, parts, ingredients, materials, or combinations thereof described in the specification, but it should be understood that these terms do not preclude the presence or addition of one or more other features, numbers, steps, operations, components, parts, ingredients, materials, or combinations thereof. The " / " used below can be interpreted as "and" or "or" depending on the circumstances.
[0021] In order to clearly represent various layers and regions in the drawings, the thickness is enlarged or reduced. Throughout the specification, similar components are given the same reference numerals. Throughout the specification, when components such as layers, films, regions, plates, etc. are referred to as "on" or "above" another component, this includes not only the situation where it is directly on the top of the other component, but also the situation where other parts are between them. Throughout the specification, terms such as first, second, etc. can be used to describe various components, but components should not be limited by the terms. Terms are only used to distinguish one component from another component. In this specification and the drawings, components with substantially the same functional configuration are given the same reference numerals, and redundant descriptions are omitted.
[0022] In the present disclosure, the "particle size" of a particle refers to the average diameter when the particle is spherical, and refers to the average major axis length when the particle is non-spherical. The particle size of the particle can be measured using a particle size analyzer (PSA). For example, the "particle size" of a particle is the average particle size. For example, the "average particle size" is the median particle size (D50). For example, the median particle size (D50) is the size of the particle corresponding to 50% cumulative volume calculated from the side of the particle with a smaller particle size in the size distribution of the particles measured by laser diffraction.
[0023] In the present disclosure, "metal" includes metals and metalloids (such as silicon and germanium) in an elemental state or an ionic state.
[0024] In this disclosure, "alloy" refers to a mixture of two or more metals.
[0025] In the present disclosure, “positive electrode active material” refers to a positive electrode material that is capable of undergoing lithiation and delithiation.
[0026] In the present disclosure, “negative electrode active material” refers to a negative electrode material that can undergo lithiation and delithiation.
[0027] In the present disclosure, "lithiation" and its variations refer to a process of adding lithium to a positive electrode active material or a negative electrode active material.
[0028] In the present disclosure, "delithiation" and its variations refer to the process of removing lithium from a positive electrode active material or a negative electrode active material.
[0029] In this disclosure, "charging" and variations thereof refers to the process of providing electrochemical energy to a battery.
[0030] In this disclosure, "discharge" and variations thereof refer to the process of removing electrochemical energy from a battery.
[0031] In this disclosure, "positive electrode" and variations thereof refer to the electrode that undergoes electrochemical reduction and lithiation during the discharge process.
[0032] In this disclosure, "negative electrode" and variations thereof refer to the electrode that undergoes electrochemical oxidation and delithiation during the discharge process.
[0033] Hereinafter, a lithium metal battery and a method for manufacturing the lithium metal battery according to example embodiments will be described in more detail.
[0034] [Lithium Metal Battery] The lithium metal battery according to the embodiment includes a positive electrode, a negative electrode and an electrolyte disposed between the positive electrode and the negative electrode, wherein the negative electrode includes lithium metal, the electrolyte includes a positive electrode electrolyte disposed adjacent to the positive electrode and a negative electrode electrolyte disposed between the positive electrode electrolyte and the negative electrode, the positive electrode electrolyte includes a first polymer electrolyte, the first polymer electrolyte includes a first polymer, and the first polymer includes a first repeating unit derived from a first single ion conductive monomer and a second repeating unit derived from a first cross-linking monomer having a plurality of reactive functional groups. The electrolyte includes a positive electrode electrolyte adjacent to the positive electrode and a negative electrode electrolyte adjacent to the negative electrode, thereby preventing degradation of the electrolyte in the high voltage positive electrode and inhibiting the growth of lithium dendrites on the surface of the negative electrode. As a result, degradation of the lithium metal battery is prevented, and the cycle characteristics of the lithium metal battery are improved.
[0035] Figure 1 is a schematic cross-sectional view of a lithium metal battery according to an embodiment.
[0036] Reference Figure 1 The lithium metal battery 1 includes a positive electrode 10, a negative electrode 20 and an electrolyte 30 arranged between the positive electrode 10 and the negative electrode 20, wherein the negative electrode 20 includes lithium metal, the electrolyte 30 includes a positive electrode electrolyte 30a arranged adjacent to the positive electrode 10 and a negative electrode electrolyte 30b arranged between the positive electrode electrolyte 30a and the negative electrode 20, the positive electrode electrolyte 30a includes a first polymer electrolyte, the first polymer electrolyte includes a first polymer, and the first polymer includes a first repeating unit derived from a first single ion conductive monomer and a second repeating unit derived from a first cross-linking monomer having multiple reactive functional groups.
[0037] [Electrolytes] Reference Figure 1 The lithium metal battery 1 includes a positive electrode 10, a negative electrode 20, and an electrolyte 30 disposed between the positive electrode 10 and the negative electrode 20. The electrolyte 30 includes a positive electrode electrolyte 30a disposed adjacent to the positive electrode 10 and a negative electrode electrolyte 30b disposed between the positive electrode electrolyte 30a and the negative electrode 20.
[0038] [Electrolyte: cathode electrolyte] The positive electrode electrolyte 30a includes a first polymer electrolyte, and the first polymer electrolyte includes a first polymer. The first polymer includes a first repeating unit derived from a first single ion conductive monomer and a second repeating unit derived from a first cross-linking monomer having a plurality of reactive functional groups. The first polymer includes the first repeating unit, thereby providing high ion conductivity and increased lithium ion conductivity. As a result, the internal resistance of the lithium metal battery including the positive electrode electrolyte 30a is reduced. Since the first polymer includes the second repeating unit, the positive electrode electrolyte has a strong cross-linking structure, thereby effectively adapting to the volume change of the lithium metal battery during charging and discharging and effectively preventing poor contact between the positive electrode active material and the positive electrode electrolyte.
[0039] The first polymer includes a first repeating unit derived from a first single ion conducting monomer.
[0040] The first single ion conductive monomer may include, for example, a reactive functional group, an anion functional group, and a counter cation in the monomer molecule. Since the anion functional group of the first single ion conductive monomer is fixed in the first polymer in the positive electrode electrolyte 30a, the counter cation can be more effectively transferred and / or diffused in the positive electrode electrolyte 30a.
[0041] The first single ion conductive monomer includes a reactive functional group, and the reactive functional group is a functional group of the first repeating unit of the first polymer formed by a cross-linking reaction with a cross-linking agent and / or another monomer. The cross-linking reaction is a thermal cross-linking reaction, an ultraviolet cross-linking reaction, etc., but is not limited thereto, and any cross-linking reaction used in the relevant technical field can be used. For example, the reactive functional group is a functional group including a double bond. The reactive functional group includes but is not necessarily limited to vinyl, acrylic, methacrylic, (4-vinyl) phenyl or a combination thereof, and any group used as a reactive functional group in the relevant technical field can be used.
[0042] The first single ion conductive monomer includes an anion functional group, and the anion functional group is a functional group capable of forming anions in the positive electrode electrolyte 30a. The anion functional group includes but is not necessarily limited to a carboxyl group, a sulfonic acid group, a sulfonimide group, or a combination thereof, and any anion functional group used in the related art can be used.
[0043] The first single ion conducting monomer includes a counter cation, and for example, the counter cation is an alkali metal cation, for example, a lithium cation, a sodium cation, a potassium cation, a rubidium cation, a cesium cation, or a combination thereof.
[0044] In the first single ion conducting monomer, the anion functional group is fixed in the monomer molecule, and the counter cation is not fixed in the monomer molecule. Therefore, in the first polymer including the first repeating unit derived from the first single ion conducting monomer including the counter cation, the conduction efficiency of the counter ion can be improved. For example, the first polymer includes a polymer network and a plurality of counter ions dispersed in the polymer network, the polymer network including a plurality of anion functional groups fixed thereto, wherein the counter ions can move and / or transfer relatively freely in the polymer network.
[0045] For example, the content of the alkali metal cation included in the first polymer is 0.1 mol to 1 mol, 0.5 mol to 1 mol, 0.8 mol to 1 mol, or 0.9 mol to 1 mol, per 1 mol of the first repeating unit.
[0046] The first polymer includes a second repeating unit derived from a first cross-linking monomer having a plurality of reactive functional groups.
[0047] The first crosslinking monomer may include, for example, two or more, three or more, or four or more reactive functional groups. As the number of reactive functional groups included in the first crosslinking monomer increases, the first crosslinking monomer may form a more rigid crosslinked product with the first single ion conductive monomer. As a result, because the first polymer including the first repeating unit and the second repeating unit has a more rigid structure, the durability of the positive electrode electrolyte 30a including the first polymer may be improved. The number of reactive functional groups included in one first crosslinking monomer may be, for example, 2 to 10, 3 to 8, or 4 to 6.
[0048] The first crosslinking monomer may be a monomer including an ester group. Since the first crosslinking monomer includes an ester group, the oxidation resistance of the positive electrode electrolyte can be further improved. Therefore, the side reaction between the positive electrode electrolyte and the positive electrode and / or the side reaction between the positive electrode electrolyte and the solvent can be more effectively suppressed by preventing oxidation of the positive electrode electrolyte in the high voltage positive electrode. As a result, the degradation of the positive electrode electrolyte can be prevented.
[0049] The first crosslinking monomer may include, for example, an acrylic monomer including a plurality of acrylic groups, a methacrylic monomer including a plurality of methacrylic groups, or a combination thereof. The first crosslinking monomer may include, for example, polycaprolactone diacrylate, polycaprolactone dimethacrylate, pentaerythritol tetraacrylate, pentaerythritol tetramethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, or a combination thereof.
[0050] The first crosslinking monomer may not be, for example, a diol monomer. The first crosslinking monomer may be, for example, a monomer that does not contain an alkylene oxide repeating unit. A diol monomer comprising an alkylene oxide repeating unit has poor oxidation resistance. Therefore, a polymer comprising a repeating unit derived from a diol monomer may be easily oxidized at a high voltage, thereby degrading the positive electrode electrolyte. For example, the alkylene oxide repeating unit is an ethylene oxide repeating unit.
[0051] A molar ratio of the first repeating unit and the second repeating unit included in the first polymer may be, for example, 99:1 to 1:99, 90:10 to 50:50, 90:10 to 66:33, 90:10 to 75:25, or 99:1 to 80:20.
[0052] The molecular weight of the first polymer can be, for example, 1000 Daltons or more, 10,000 Daltons or more, or 100,000 Daltons or more. The molecular weight of the first polymer can be, for example, 1000 Daltons to 5,000,000 Daltons, 10,000 Daltons to 2,000,000 Daltons, or 100,000 Daltons to 1,000,000 Daltons. The first polymer can have a two-dimensional and / or three-dimensional network structure in the first polymer electrolyte.
[0053] Relative to the total weight of the first polymer electrolyte, the content of the first polymer may be, for example, 0.2wt% to 10wt%, 0.5wt% to 5wt%, 1wt% to 4wt% or 2wt% to 3wt%. Since the first polymer electrolyte includes the first polymer within this range, a gel polymer electrolyte may be formed. When the content of the first polymer is too low, it may be difficult to form a gel. When the content of the first polymer is too high, the first polymer electrolyte may harden, resulting in cracks in the first polymer electrolyte during the charge and discharge process.
[0054] The first polymer electrolyte may further include, for example, at least one selected from a first inorganic solid electrolyte, a first filler, a first organic solvent, and a first lithium salt.
[0055] Since the first polymer electrolyte also includes a first inorganic solid electrolyte, the elastic modulus of the first polymer electrolyte can be increased, and the ionic conductivity of the first polymer electrolyte can be increased. Since the first polymer electrolyte additionally includes a first inorganic solid electrolyte, the internal resistance of the lithium metal battery including the positive electrode electrolyte can be further reduced, and the short circuit between the positive electrode and the negative electrode can be more effectively suppressed. The first inorganic solid electrolyte can be, for example, an oxide solid electrolyte or a sulfide solid electrolyte. The first inorganic solid electrolyte can be selected from the second inorganic solid electrolyte used in the negative electrode electrolyte. The first inorganic solid electrolyte can be omitted.
[0056] Since the first polymer electrolyte includes the first filler, the elastic modulus of the first polymer electrolyte can be increased. Since the first polymer electrolyte has an increased elastic modulus, a short circuit between the positive electrode and the negative electrode due to the growth of lithium dendrites can be more effectively prevented. The first filler can be selected from the second filler used in the negative electrode electrolyte. The first filler can be omitted.
[0057] Since the first polymer electrolyte also includes a first organic solvent, the flexibility of the first polymer electrolyte can be increased, and the interface resistance between the first polymer electrolyte and the positive electrode active material can be further reduced. The first organic solvent can be a carbonate organic solvent, but it is not necessarily limited thereto, and any organic solvent used in lithium batteries in the relevant technical field can be used. The organic solvent is, for example, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dioxane, 1,2-dimethoxyethane, cyclopentane, dichloroethane, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether, or a mixture thereof. The carbonate-based organic solvent may include, for example, ethylene carbonate, propylene carbonate, fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, or a combination thereof.
[0058] Since the first polymer electrolyte also includes a first lithium salt, the ion conductivity of the first polymer electrolyte can be improved. The first lithium salt can be any lithium salt used in the relevant technical field. The first lithium salt includes, for example, LiBF4, LiPF6, LiClO4, LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiC(CF2SO2)3, LiBF2(C2O4), LiSbF6, LiAsF6, LiC4F9SO3, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (1≤x≤20, 1≤y≤20), LiCl, LiI, or a combination thereof. The concentration of the first lithium salt is, for example, 0.1M to 5.0M.
[0059] The positive electrode electrolyte 30a may not contain a compound including an alkylene oxide repeating unit. Since the compound including the alkylene oxide repeating unit has poor oxidation resistance, the compound may be oxidized at a high voltage, thereby deteriorating the positive electrode electrolyte 30a. The compound including the alkylene oxide repeating unit may be, for example, a monomer including an alkylene oxide repeating unit, an oligomer including an alkylene oxide repeating unit, a polymer including an alkylene oxide repeating unit, or a combination thereof. The alkylene oxide group may be, for example, an ethylene oxide group. The oligomer including the alkylene oxide repeating unit may be, for example, polyethylene glycol. The polymer including the alkylene oxide repeating unit may be, for example, polyethylene oxide.
[0060] The positive electrode electrolyte 30a may be an organic electrolyte. The positive electrode electrolyte 30a may be an organic electrolyte that does not include inorganic particles and is made of an organic material.
[0061] Reference Figure 3 The positive electrode electrolyte 30a may have a current density of 0.003 mA / cm at 5.0 V relative to lithium metal as measured by linear sweep voltammetry (LSV) at a scan rate of 1 mV / s. 2 or less. Since the positive electrode electrolyte 30a has a 0.003 mA / cm 2 The low current density is 2.0 V or less, and therefore it is found that the side reaction is effectively suppressed in this voltage range. Since the positive electrode electrolyte 30a has a wide voltage window of 5.0 V relative to lithium metal, the positive electrode electrolyte 30a can be appropriately used as a positive electrode electrolyte for a lithium metal battery having a positive electrode operating at a high voltage of 3.0 V or more.
[0062] At 25°C, the ionic conductivity of the positive electrode electrolyte 30a may be, for example, 2×10 -4 S / cm or more, 2.2×10 -4 S / cm or greater, or 2.4×10 -4 S / cm or more. Since the positive electrode electrolyte 30a has a 2×10 -4 S / cm or more, and thus the ionic conductivity of the positive electrode electrolyte 30a can be improved, and the internal resistance of the lithium metal battery including the positive electrode electrolyte 30a can be further reduced.
[0063] At 25° C., the lithium ion transference number of the positive electrode electrolyte 30a may be, for example, 0.3 or more, 0.32 or more, or 0.34 or more. Since the positive electrode electrolyte 30a has a lithium ion transference number of 0.3 or more, the conduction efficiency of lithium ions in the positive electrode electrolyte 30a may be improved, and the internal resistance of the lithium metal battery including the positive electrode electrolyte 30a may be reduced.
[0064] At 25°C, the lithium ion conductivity of the positive electrode electrolyte 30a may be, for example, 6×10 -5 S / cm or more, 7×10 -5 S / cm or more, or 8×10 -5 S / cm or more. Since the positive electrode electrolyte 30a has a 6×10 -5 S / cm or more, the lithium ion conductivity of the positive electrode electrolyte 30a can be improved, and the internal resistance of the lithium metal battery including the positive electrode electrolyte 30a can be further reduced.
[0065] [Electrolyte: porous support] The lithium metal battery 1 may further include a porous support 40 disposed between the positive electrode 10 and the negative electrode 20. The electrolyte 30 may be impregnated into the porous support 40.
[0066] The porous support 40 can be, for example, a porous membrane. The porous membrane can be, for example, a woven or non-woven fabric. Any porous membrane commonly used in lithium batteries can be used. The porous membrane can include, for example, glass fiber, olefin resin, fluororesin, ester resin, imide resin, acrylic resin, cellulose resin, or a combination thereof. Olefin resin can include, for example, polyethylene, polypropylene, or a combination thereof. Fluororesin can include, for example, polyvinylidene fluoride, polytetrafluoroethylene, or a combination thereof. Ester resin can include, for example, polyethylene terephthalate, polybutylene terephthalate, or a combination thereof. Imide resin can include, for example, polyamide-imide, polyetherimide, or a combination thereof. Acrylic resin can include, for example, polyacrylonitrile, polyacrylate, or a combination thereof. Cellulose resin can include, for example, microbial cellulose, plant cellulose, animal cellulose, or a combination thereof.
[0067] The porous support 40 may be impregnated with the positive electrode electrolyte 30a. The composition for forming the positive electrode electrolyte may be injected into the porous support and then cured to prepare the positive electrode electrolyte 30a impregnated into the porous support. A porous film having excellent impregnation ability for the composition for forming the positive electrode electrolyte including the first organic solvent may be used as the porous support 40. The porous support 40 may be, for example, a separator.
[0068] The porous film is formed by the following exemplified methods, but the formation of the porous film is not necessarily limited to these methods and can be adjusted according to desired conditions.
[0069] First, a polymer resin, a filler and a solvent are mixed to prepare a composition for forming a porous film. The composition for forming a porous film is directly applied to an electrode and dried to form a porous film. Alternatively, the composition for forming a porous film is cast on a support and dried, and then the porous film peeled off from the support is laminated on the electrode to form a porous film. The polymer resin for forming the porous film is not particularly limited, and the above-mentioned resins can be used. Any polymer for forming a porous film can be used as a binder for the electrode. The polymer resin for forming a porous film includes, for example, a vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, or a combination thereof.
[0070] [Electrolyte: Negative Electrolyte] Reference Figure 1 , the electrolyte 30 includes a negative electrode electrolyte 30b disposed between the positive electrode electrolyte 30a and the negative electrode 20 and disposed adjacent to the negative electrode 20. The negative electrode electrolyte 30b includes a second polymer electrolyte, and the second polymer electrolyte includes a second polymer. The second polymer includes a third repeating unit derived from a second single ion conductive monomer and a fourth repeating unit derived from a second cross-linking monomer having a plurality of reactive functional groups. The second polymer includes the third repeating unit, thereby providing high ion conductivity and increased lithium ion conductivity. As a result, the internal resistance of the lithium metal battery including the negative electrode electrolyte 30b is reduced. Since the second polymer includes the fourth repeating unit, the negative electrode electrolyte 30b has a strongly cross-linked structure, thereby effectively suppressing the formation of dendrites of the negative electrode 20 of the lithium metal during charging and discharging and effectively preventing the contact between the negative electrode 20 of the lithium metal and the positive electrode electrolyte 30a.
[0071] The second polymer includes a third repeating unit derived from a second single ion conducting monomer.
[0072] The second single ion conducting monomer may include, for example, an aromatic ring within the monomer molecule. Since the second single ion conducting monomer includes an aromatic ring, the second polymer including the third repeating unit derived from the second single ion conducting monomer may have an improved elastic modulus. Since the second polymer has an improved elastic modulus, the negative electrode electrolyte 30b may more effectively inhibit the growth of lithium dendrites. The aromatic ring included in the second single ion conducting monomer may be a hydrocarbon ring having 6 to 20 carbon atoms. The aromatic ring included in the second single ion conducting monomer may be a phenylene ring, a naphthylene ring, or a combination thereof.
[0073] The second single ion conductive monomer may include, for example, a reactive functional group, an anion functional group, and a counter cation in the monomer molecule. Since the anion functional group of the second single ion conductive monomer is fixed in the second polymer in the negative electrode electrolyte 30b, the counter cation can be more effectively transferred and / or diffused in the negative electrode electrolyte 30b.
[0074] The second single ion conductive monomer includes a reactive functional group, and the reactive functional group is a functional group of the third repeating unit of the second polymer formed by a crosslinking reaction with a crosslinking agent and / or another monomer. The crosslinking reaction is a thermal crosslinking reaction, an ultraviolet crosslinking reaction, etc., but is not limited thereto, and any crosslinking reaction used in the relevant technical field can be used. The reactive functional group includes but is not necessarily limited to vinyl, acrylic, methacrylic, (4-vinyl) phenyl or a combination thereof, and any group used as a reactive functional group in the relevant technical field can be used.
[0075] The second single ion conductive monomer includes an anion functional group, and the anion functional group is a functional group capable of forming anions in the negative electrode electrolyte 30b. The anion functional group includes but is not necessarily limited to a carboxyl group, a sulfonic acid group, a sulfonimide group, or a combination thereof, and any anion functional group used in the related art can be used.
[0076] The second single ion conducting monomer includes a counter cation, and for example, the counter cation is an alkali metal cation, for example, a lithium cation, a sodium cation, a potassium cation, a rubidium cation, a cesium cation, or a combination thereof.
[0077] For example, the content of the alkali metal cation included in the second polymer is 0.1 mol to 1 mol, 0.5 mol to 1 mol, 0.8 mol to 1 mol, or 0.9 mol to 1 mol, per 1 mol of the first repeating unit.
[0078] The second polymer includes a fourth repeating unit derived from a second cross-linking monomer having a plurality of reactive functional groups.
[0079] The second crosslinking monomer may include, for example, two or more, three or more, or four or more reactive functional groups. As the number of reactive functional groups included in the second crosslinking monomer increases, the second crosslinking monomer may form a more rigid crosslinked product with the second single ion conductive monomer. As a result, because the second polymer including the third repeating unit and the fourth repeating unit has a more rigid structure, the durability of the negative electrode electrolyte 30b including the second polymer may be improved. The number of reactive functional groups included in one second crosslinking monomer may be, for example, 2 to 10, 3 to 8, or 4 to 6.
[0080] The second cross-linking monomer may be a monomer including an aromatic ring. Since the second cross-linking monomer includes an aromatic ring, the second polymer including the fourth repeating unit derived from the second cross-linking monomer may have an improved elastic modulus. Since the second polymer has an improved elastic modulus, the negative electrode electrolyte 30b may more effectively inhibit the growth of lithium dendrites. The aromatic ring included in the second cross-linking monomer may be a hydrocarbon ring having 6 to 20 carbon atoms. The aromatic ring included in the second single ion conductive monomer may be a phenylene ring, a naphthylene ring, or a combination thereof.
[0081] The second crosslinking monomer may include, for example, a vinyl monomer including multiple vinyl groups, an acrylic monomer including multiple acrylic groups, a methacrylic monomer including multiple methacrylic groups, or a combination thereof. The second crosslinking monomer may include, for example, 1,3-divinylbenzene, 1,4-divinylbenzene, 2,7-divinylnaphthalene, 1,9-divinylnaphthalene, p-xylene diacrylate, o-xylene diacrylate, m-xylene diacrylate, p-xylene dimethacrylate, o-xylene dimethacrylate, m-xylene dimethacrylate, naphthalene-1,5-diyl diacrylate, naphthalene-1,9-diyl diacrylate, or a combination thereof.
[0082] The molar ratio of the third repeating unit and the fourth repeating unit included in the second polymer is, for example, 99:1 to 1:99, 90:10 to 50:50, 90:10 to 66:33, 90:10 to 75:25, or 99:1 to 80:20.
[0083] The molecular weight of the second polymer can be, for example, 1000 Daltons or greater, 10,000 Daltons or greater, or 100,000 Daltons or greater.The molecular weight of the second polymer can be, for example, 1000 Daltons to 5,000,000 Daltons, 10,000 Daltons to 2,000,000 Daltons, or 100,000 Daltons to 1,000,000 Daltons.
[0084] Relative to the total weight of the second polymer electrolyte, the content of the second polymer can be, for example, 0.2wt% to 10wt%, 0.5wt% to 5wt%, 1wt% to 4wt% or 2wt% to 3wt%. Since the second polymer electrolyte includes the second polymer within this range, a gel polymer electrolyte can be formed. When the content of the second polymer is too low, it may be difficult to form a gel, or the elastic modulus of the negative electrode electrolyte may be excessively reduced, making it difficult to inhibit the growth of lithium dendrites. When the content of the second polymer is too high, the second polymer electrolyte hardens and cracks appear in the second polymer electrolyte during the charge-discharge process, and lithium dendrites may grow through these cracks.
[0085] The second polymer electrolyte may further include at least one selected from, for example, a second inorganic solid electrolyte, a second filler, a second lithium salt, and a third polymer.
[0086] Since the second polymer electrolyte further includes the second inorganic solid electrolyte, the elastic modulus of the second polymer electrolyte can be increased, and the ionic conductivity of the second polymer electrolyte can be increased. Since the second polymer electrolyte further includes the second inorganic solid electrolyte, the internal resistance of the lithium metal battery 1 including the negative electrode electrolyte 30b can be further reduced, and the short circuit between the positive electrode 10 and the negative electrode 20 can be more effectively suppressed.
[0087] The second inorganic solid electrolyte may be, for example, an oxide-based solid electrolyte. The oxide-based solid electrolyte is, for example, selected from Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (0 < x < 2, 0 ≤ y < 3), BaTiO3, Pb(Zr, Ti)O3 (PZT), Pb 1-x La x Zr 1- y Ti y O3 (PLZT) (0 ≤ x < 1, 0 ≤ y < 1), Pb(Mg3Nb 2 / 3 )O3 - PbTiO3 (PMN - PT), HfO2, SrTiO3, SnO2, CeO2, Na2O, MgO, NiO, CaO, BaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiO2, Li3PO4, Li x Ti y (PO4)3 (0 < x < 2, 0 < y < 3), Li x Al y Ti z (PO4)3 (0 < x < 2, 0 < y < 1, 0 < z < 3), Li 1+x+y (Al, Ga) x (Ti, Ge) 2-x Si y P 3-y O 12 (0 ≤ x ≤ 1, 0 ≤ y ≤ 1), Li x La y TiO3 (0 < x < 2, 0 < y < 3), Li2O, LiOH, Li2CO3, LiAlO2, Li2O - Al2O3 - SiO2 - P2O5 - TiO2 - GeO2, and Li 3+x La3M2O 12(M = Te, Nb or Zr, 1 ≤ x ≤ 10). The solid electrolyte can be prepared by, for example, a sintering method. The oxide solid electrolyte is, for example, selected from Li7La3Zr2O 12 (LLZO) and Li 3+x Ln3Z 2-a M a O 12 Garnet-type solid electrolyte in (M-doped LLZO, M=Ga, W, Nb, Ta or Al, 1≤x≤10).
[0088] The particle size of the oxide solid electrolyte is, for example, 10 nm to 5 μm, 50 nm to 3 μm, 100 nm to 1 μm, 100 nm to 900 nm, 200 nm to 800 nm, or 400 nm to 800 nm. Since the oxide solid electrolyte has a particle size within this range, the elastic modulus of the negative electrode electrolyte 30 b can be further improved.
[0089] The content of the second inorganic solid electrolyte included in the second polymer electrolyte may be, for example, 1 wt % to 60 wt %, 5 wt % to 60 wt %, 5 wt % to 50 wt %, or 10 wt % to 40 wt % relative to the total weight of the second polymer electrolyte. Since the second polymer electrolyte includes the second inorganic solid electrolyte within this range, the elastic modulus of the negative electrode electrolyte 30 b can be further increased.
[0090] Since the second polymer electrolyte includes the second filler, the elastic modulus of the second polymer electrolyte may be increased. Since the second polymer electrolyte has an increased elastic modulus, a short circuit between the positive electrode 10 and the negative electrode 20 due to the growth of lithium dendrites may be more effectively prevented.
[0091] The second filler may be, for example, inorganic particles. The inorganic particles may include, but are not necessarily limited to, at least one selected from metal oxides, carbon oxides, carbonaceous materials, and organic-inorganic composites, and any particles in the relevant technical field that can improve the ionic conductivity of the second polymer electrolyte and increase the mechanical strength of the second polymer electrolyte may be used.
[0092] The inorganic particles may include, for example, metal oxides. The metal oxides may be composed of, for example, a O cis represented by (0 < a ≤ 3, 0 < c ≤ 5, where M is at least one metal selected from Groups 2 to 16 of the periodic table). The metal oxide may be selected from, for example, Al2O3, NbO, NbO2, Nb2O5, MgO, Sc2O3, TiO2, ZrO2, V2O3, WO2, MnO2, Fe2O3, Co3O4, PdO, CuO, AgO, ZnO, Sb2O3, SiO2, SeO2, BaTiO3, and metal-organic frameworks (MOFs). The inorganic particles may include, for example, carbon oxides, carbonaceous materials, or organic-inorganic composites. The inorganic particles may include at least one selected from, for example, graphite oxide, graphene oxide, polyhedral oligomeric silsesquioxane (POSS), Li2CO3, Li3PO4, Li3N, Li3S4, Li2O, and montmorillonite.
[0093] The particle size of the inorganic particles is, for example, 1 nm to 1 μm, 5 nm to 800 nm, 10 nm to 600 nm, 15 nm to 500 nm, or 20 nm to 400 nm. Since the inorganic particles have a particle size within this range, the elastic modulus of the negative electrode electrolyte 30b can be further increased.
[0094] The inorganic particles may be, for example, porous. The inorganic particles may be, for example, mesoporous particles.
[0095] The content of the second filler included in the second polymer electrolyte may be, for example, 1 wt% to 20 wt%, 3 wt% to 15 wt%, or 5 wt% to 15 wt% relative to the total weight of the second polymer electrolyte. Since the second polymer electrolyte includes the second filler within this range, the elastic modulus of the negative electrode electrolyte 30b can be further increased.
[0096] The second filler may be, for example, a reactive filler having reactive functional groups on its surface. The reactive filler may be, for example, a reactive metal oxide having reactive functional groups on its surface.
[0097] The reactive functional groups included in the second filler are functional groups including double bonds and may be, for example, vinyl, acrylic, methacrylic, or a combination thereof.
[0098] The second polymer electrolyte includes the second filler and the second polymer, and the second filler may be chemically bonded to the second polymer through the reactive functional groups provided on the surface of the second filler. Since the second filler and the second polymer are chemically crosslinked, the elastic modulus of the second polymer electrolyte can be further increased. Therefore, the negative electrode electrolyte 30b can more effectively prevent a short circuit between the positive electrode and the negative electrode due to the growth of lithium dendrites.
[0099] Since the second polymer electrolyte includes the second lithium salt, the ion conductivity of the second polymer electrolyte can be improved. As the second lithium salt, any lithium salt used in the relevant technical field can be used. The second lithium salt includes, for example, LiBF4, LiPF6, LiClO4, LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiC(CF2SO2)3, LiBF2(C2O4), LiSbF6, LiAsF6, LiC4F9SO3, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (1≤x≤20, 1≤y≤20), LiCl, LiI, or a combination thereof. The content of the second lithium salt may be, for example, 1 wt % to 30 wt %, 10 wt % to 25 wt %, or 15 wt % to 25 wt % relative to the total weight of the second polymer electrolyte.
[0100] The second polymer electrolyte may further include a third polymer. The third polymer is, for example, an ion-conducting polymer. The third polymer may have ion conductivity and may be a polymer with high stability to lithium metal. The third polymer may, for example, be used to transfer ions across the surface of lithium metal. The third polymer may, for example, be used to block contact between the negative electrode and the positive electrode electrolyte.
[0101] The ion-conducting polymer may be, for example, polystyrene sulfonate (PSS), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) copolymer, polyvinyl fluoride (PVF), polyvinylidene fluoride (PVDF), poly(methyl methacrylate) (PMMA), polyethylene oxide (PEO), polyacrylonitrile (PAN), polytetrafluoroethylene (PTFE), polyethylenedioxythiophene (PEDOT), polypyrrole (PPY), polyacrylonitrile (PAN), polyaniline, polyacetylene, or a combination thereof.
[0102] The third polymer may be an ion-conducting polymer including alkylene oxide repeating units. The alkylene oxide repeating units may be ethylene oxide repeating units. The third polymer may be, for example, polyethylene oxide. The molecular weight of the polyethylene oxide may be, for example, 1,000 Daltons to 500,000 Daltons.
[0103] The third polymer may be contained in an amount of, for example, 1 wt % to 50 wt %, 10 wt % to 50 wt %, 20 wt % to 50 wt %, 20 wt % to 40 wt %, or 30 wt % to 40 wt % of the total weight of the second polymer electrolyte.
[0104] The electrolyte 30 includes a positive electrode electrolyte 30a and a negative electrode electrolyte 30b, and each of the positive electrode electrolyte 30a and the negative electrode electrolyte 30b may be a polymer gel electrolyte. Since the electrolyte 30 is a polymer gel electrolyte, a short circuit between the positive electrode 10 and the negative electrode 20 due to the growth of lithium dendrites can be more effectively prevented, and risks such as electrolyte leakage can be suppressed.
[0105] The elastic modulus of the negative electrode electrolyte 30b may be greater than that of the positive electrode electrolyte 30a. Since the negative electrode electrolyte 30b is an organic-inorganic composite electrolyte including inorganic particles, the negative electrode electrolyte 30b may have a higher elastic modulus than the positive electrode electrolyte 30a. Since the negative electrode electrolyte 30b has a larger elastic modulus than the positive electrode electrolyte 30a, the side reaction between the positive electrode electrolyte 30a and the lithium metal can be effectively blocked.
[0106] The difference between the elastic modulus of the negative electrode electrolyte 30 b and the elastic modulus of the positive electrode electrolyte 30 a may be 1 MPa or more, 10 MPa or more, 100 MPa or more, or 1 GPa or more.
[0107] Since the negative electrode electrolyte 30 b has a relatively high elastic modulus, the growth of lithium dendrites can be more effectively suppressed, and a short circuit between the positive electrode 10 and the negative electrode 20 can be effectively prevented.
[0108] The thickness of the positive electrode electrolyte 30a may be greater than that of the negative electrode electrolyte 30b. Since the thickness of the positive electrode electrolyte 30a is greater than that of the negative electrode electrolyte 30b, a short circuit between the positive electrode 10 and the negative electrode 20 may be more effectively prevented.
[0109] The thickness of the lithium metal may be greater than the thickness of the negative electrode electrolyte 30 b. Since the thickness of the lithium metal is greater than the thickness of the negative electrode electrolyte 30 b, the energy density of the lithium metal battery 1 may be increased.
[0110] The thickness of the positive electrode electrolyte 30a may be, for example, the thickness of the positive electrode electrolyte 30a impregnated in the porous support. The thickness of the positive electrode electrolyte 30a may be, for example, the thickness of the porous support. The thickness of the positive electrode electrolyte 30a may be, for example, the thickness of the separator.
[0111] The thickness of the positive electrode electrolyte 30a is, for example, 5 μm to 50 μm, 5 μm to 40 μm, 5 μm to 30 μm, or 8 μm to 25 μm. Since the positive electrode electrolyte 30a has a thickness within this range, a short circuit between the positive electrode 10 and the negative electrode 20 can be effectively prevented. When the thickness of the positive electrode electrolyte 30a is excessively increased, the energy density of the lithium metal battery 1 may be reduced. When the thickness of the positive electrode electrolyte 30a is excessively reduced, the possibility of a short circuit between the positive electrode 10 and the negative electrode 20 may increase.
[0112] The thickness of the lithium metal may be, for example, 1 μm to 500 μm, 5 μm to 300 μm, or 10 μm to 200 μm. When the thickness of the lithium metal is too thin, the cycle characteristics of the lithium metal battery deteriorate. When the thickness of the lithium metal is too thick, the volume change of the lithium metal battery increases excessively during charging and discharging, making it difficult to maintain mechanical stability, and the efficiency of active material utilization may be reduced due to the use of excessive active materials.
[0113] The thickness of the negative electrode electrolyte 30b may be, for example, 1 μm to 50 μm, 1 μm to 30 μm, or 1 μm to 20 μm. Since the negative electrode electrolyte 30b has a thickness within this range, the reduction in energy density of the lithium metal battery can be minimized and the growth of lithium dendrites can be effectively suppressed.
[0114] [positive electrode] Reference Figure 1 , the lithium metal battery 1 according to the embodiment includes a positive electrode 10 , and the positive electrode 10 includes a positive electrode collector 11 and a positive electrode active material layer 12 disposed on one side of the positive electrode collector 11 .
[0115] [Positive electrode: positive electrode active material layer] The positive electrode active material layer 12 includes a positive electrode active material. The positive electrode active material may be any material used in the relevant technical field, for example, a lithium-containing metal oxide. As the positive electrode active material, for example, at least one of a composite oxide of lithium and a metal selected from cobalt, manganese, nickel, and a combination thereof may be used, and as a specific example, the composite oxide may be a composite oxide composed of Li a A 1-b B b D2 (where 0.90≤a≤1, 0≤b≤0.5), Li a E 1-b B b O 2-c D c (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05), LiE 2-b B b O 4-c D c (where 0≤b≤0.5, 0≤c≤0.05), Li a Ni 1-b-c Co b B c D α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, 0<α≤2), Li a Ni 1-b-c Co b B c O 2-αF α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, 0<α<2), Li a Ni 1-b-c Co b B c O 2-α F2 (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, 0<α<2), Li a Ni 1-b-c Mn b B c D α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, 0<α≤2), Li a Ni 1-b-c Mn b B c O 2-α F α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, 0<α<2), Li a Ni 1-b-c Mn b B c O 2-α F2 (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, 0<α<2), Li a Ni b E c G d O2 (where 0.90≤a≤1, 0≤b≤0.9, 0≤c≤0.5, 0.001≤d≤0.1), Li a Ni b Co c Mn d G e O2 (where 0.90≤a≤1, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, 0.001≤e≤0.1), Li a NeG b O2 (where 0.90≤a≤1, 0.001≤b≤0.1), Li a CoG b O2 (where 0.90≤a≤1, 0.001≤b≤0.1), Li a MnG b O2 (where 0.90≤a≤1, 0.001≤b≤0.1), Li a Mn bO4 (where 0.90≤a≤1, 0.001≤b≤0.1), QO2, QS2, LiQS2, V2O5, LiV2O5, LiIO2, LiNiVO4, Li (3-f) J2(PO4)3(0≤f≤2)、Li (3-f) A compound represented by any of the molecular formulas of Fe2(PO4)3 (0≤f≤2) and LiFePO4.
[0116] In the molecular formula representing the above-mentioned compound, A is Ni, Co, Mn or a combination thereof; B is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element or a combination thereof; D is O, F, S, P or a combination thereof; E is Co, Mn or a combination thereof; F is F, S, P or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; Q is Ti, Mo, Mn or a combination thereof; I is Cr, V, Fe, Sc, Y or a combination thereof; and J is V, Cr, Mn, Co, Ni, Cu or a combination thereof. Compounds having a coating added to the surface of the above-mentioned compound can also be used, and mixtures of the above-mentioned compound and compounds having a coating added thereto can also be used. The coating added to the surface of the above-mentioned compound includes a coating element compound of an oxide of the coating element, a coating element compound of a hydroxide of the coating element, a coating element compound of an oxyhydroxyl of the coating element, a coating element compound of an oxycarbonate of the coating element, or a coating element compound of a hydroxycarbonate of the coating element. The compound forming the coating is amorphous or crystalline. The coating element included in the coating is Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr or a mixture thereof. The method for forming the coating is selected within the range that does not adversely affect the physical properties of the positive electrode active material. The coating method is, for example, spraying, dipping, etc. Since the specific coating method is well understood by those skilled in the art, a detailed description will be omitted.
[0117] The positive electrode active material is, for example, Li a Ni x Co y M z O 2-b A b(1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0.8 ≤ x < 1, 0 < y ≤ 0.3, 0 < z ≤ 0.3, and x + y + z = 1, where M is manganese (Mn), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B), or a combination thereof, and A is F, S, Cl, Br, or a combination thereof), LiNi x Co y Mn z O2 (0.8 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.2, 0 < z ≤ 0.2, and x + y + z = 1), LiNi x Co y Al z O2 (0.8 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.2, 0 < z ≤ 0.2, and x + y + z = 1), LiNi x Co y Mn z Al w O2 (0.8 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.2, 0 < z ≤ 0.2, 0 < w ≤ 0.2, and x + y + z + w = 1), Li a Co x M y O 2-b A b (1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0.9 ≤ x ≤ 1, 0 ≤ y ≤ 0.1, and x + y = 1, where M is manganese (Mn), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B), or a combination thereof, and A is F, S, Cl, Br, or a combination thereof), Li a Ni x Mn y M' z O 2-b A b (1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0 < x ≤ 0.3, 0.5 ≤ y < 1, 0 < z ≤ 0.3, and x + y + z = 1, where M' is cobalt (Co), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B), or a combination thereof, and A is F, S, Cl, Br, or a combination thereof), Li a M1 x M2 y PO 4-b Xb (0.90 ≤ a ≤ 1.1, 0 ≤ x ≤ 0.9, 0 ≤ y ≤ 0.5, 0.9 < x + y < 1.1, 0 ≤ b ≤ 2, M1 is chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zirconium (Zr) or a combination thereof, M2 is magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), zinc (Zn), boron (B), niobium (Nb), gallium (Ga), indium (In), molybdenum (Mo), tungsten (W), aluminum (Al), silicon (Si), chromium (Cr), vanadium (V), scandium (Sc), yttrium (Y) or a combination thereof, and X is O, F, S, P or a combination thereof), Li a M3 z PO4 (0.90 ≤ a ≤ 1.1, 0.9 ≤ z ≤ 1.1, M3 is chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zirconium (Zr) or a combination thereof).
[0118] The positive electrode active material layer 12 includes a conductive material. As the conductive material, carbon black, graphite particles, natural graphite, artificial graphite, acetylene black, Ketjen black, carbon fiber; carbon nanotubes; metal powders, metal fibers or metal tubes of copper, nickel, aluminum and silver; and conductive polymers such as polyphenylene derivatives can be used, but the present disclosure is not limited thereto, and any material used as a conductive material in the related art can be used. Optionally, the positive electrode may not include an additional conductive material.
[0119] The positive electrode active material layer 12 includes, for example, a binder. As the binder, vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polytetrafluoroethylene (PTFE), a mixture of the above polymers, styrene-butadiene rubber-like polymers, etc. can be used.
[0120] Relative to the total weight of the positive electrode active material layer 12, the content of the positive electrode active material included in the positive electrode active material layer 12 may be 80 wt% to 99 wt%, 90 wt% to 99 wt% or 95 wt% to 99 wt%.
[0121] Relative to the total weight of the positive electrode active material layer 12, the content of the conductive material included in the positive electrode active material layer 12 may be 0.1 wt% to 10 wt% or 0.1 wt% to 5 wt%.
[0122] Relative to the total weight of the positive electrode active material layer 12, the content of the binder included in the positive electrode active material layer 12 may be 0.1 wt% to 10 wt% or 0.1 wt% to 5 wt%.
[0123] The contents of the positive electrode active material, the conductive material and the binder included in the positive electrode are at levels generally used in lithium batteries. Depending on the purpose and configuration of the lithium battery, one or more of the conductive material and the binder may be omitted.
[0124] [Positive electrode: positive electrode current collector] Any material constituting the positive electrode current collector 11 can be used as long as it is conductive and does not react with lithium (i.e., does not form an alloy or compound with lithium). The positive electrode current collector 11 is made of, for example, a metal or an alloy. The positive electrode current collector 11 can be made of, for example, aluminum (Al), indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), germanium (Ge) or an alloy thereof. The positive electrode current collector 11 may have a form selected from, for example, a sheet, a foil, a film, a plate, a porous body, a mesoporous body, a body including a through hole, a polygonal ring body, a mesh body, a foam body and a non-woven body, but is not necessarily limited to such a form, and any form used in the relevant technical field is possible.
[0125] [negative electrode] Reference Figure 1 , the lithium metal battery 1 according to the embodiment includes a negative electrode 20 , and the negative electrode 20 includes a negative electrode collector 21 and a negative electrode active material layer 22 disposed on one side of the negative electrode collector 21 .
[0126] [Negative electrode: negative electrode active material layer] The negative electrode active material layer 22 includes lithium metal or lithium alloy. The negative electrode active material layer 22 may include, for example, lithium foil, lithium powder, or a combination thereof. The lithium foil may include, for example, lithium metal foil, lithium alloy foil, or a combination thereof. The lithium powder may include lithium metal powder, lithium alloy powder, or a combination thereof. Lithium alloy is an alloy of lithium and other metals that can be alloyed with lithium, for example, lithium silver alloy, lithium zinc alloy, lithium magnesium alloy, lithium tin alloy, etc. The negative electrode active material layer 22 including lithium metal foil may be, for example, a lithium metal layer. The negative electrode active material layer 22 including lithium metal foil may be, for example, a lithium alloy layer. The negative electrode active material layer 22 including lithium metal powder and / or lithium alloy powder may be introduced by coating a slurry including lithium powder, a binder, etc. on the negative electrode current collector. The binder may be a fluorine-based binder, such as polyvinylidene fluoride (PVDF). The negative electrode active material layer 22 may not include a carbon-based negative electrode active material.
[0127] The thickness of the lithium metal foil may be, for example, 1 μm to 50 μm, 1 μm to 30 μm, or 1 μm to 20 μm. Since the lithium metal foil has a thickness within this range, the life characteristics of the lithium metal battery can be further improved. The particle size of the lithium metal powder may be, for example, 0.1 μm to 3 μm, 0.1 μm to 2 μm, or 0.1 μm to 2 μm. Since the lithium metal powder has a thickness within this range, the life characteristics of the lithium metal battery can be further improved. The thickness of the negative electrode active material layer 22 may be, for example, 1 μm to 100 μm, 1 μm to 80 μm, 1 μm to 60 μm, or 1 μm to 50 μm.
[0128] [Negative electrode: negative electrode current collector] The negative electrode current collector 21 includes, for example, a metal substrate. The metal substrate includes a first metal as a main component, or is made of a first metal. The content of the first metal included in the metal substrate is, for example, 90 wt% or more, 95 wt% or more, 99 wt% or more, or 99.9 wt% or more relative to the total weight of the metal substrate. The metal substrate may be composed of, for example, a material that does not react with lithium (ie, does not form an alloy and / or compound with lithium). The first metal may be, for example, copper (Cu), nickel (Ni), stainless steel (SUS), iron (Fe), or cobalt (Co), but is not necessarily limited thereto, and any metal used as a negative electrode current collector in the relevant technical field may be used. The metal substrate may be composed of, for example, one of the above metals, or an alloy of two or more metals. The metal substrate has, for example, a sheet or foil form. The thickness of the negative electrode current collector 21 may be, for example, 5 μm to 50 μm, 10 μm to 50 μm, 10 μm to 40 μm, or 10 μm to 30 μm, but is not necessarily limited to this range, and may be selected according to the desired characteristics of the lithium metal battery.
[0129] The negative electrode current collector 21 may further include a coating layer (not shown) including a second metal on the metal substrate. The negative electrode current collector 21 may include, for example, a metal substrate and a coating layer disposed on the metal substrate and including a second metal. The second metal has a Mohs hardness higher than that of the first metal. That is, since the coating layer including the second metal is harder than the metal substrate including the first metal, degradation of the metal substrate can be prevented. The Mohs hardness of the material constituting the metal substrate is, for example, 5.5 or less. The Mohs hardness of the first metal is, for example, 5.5 or less, 5.0 or less, 4.5 or less, 4.0 or less, 3.5 or less, or 3.0 or less. The Mohs hardness of the first metal may be, for example, 2.0 to 5.5. The Mohs hardness of the material constituting the coating layer is, for example, 6.0 or more. For example, the Mohs hardness of the second metal is 6.0 or more, 6.5 or more, 7.0 or more, 7.5 or more, 8.0 or more, 8.5 or more, or 9.0 or more. The Mohs hardness of the second metal may be, for example, 6.0 to 12. When the Mohs hardness of the second metal is too low, it may be difficult to suppress the degradation of the negative electrode current collector. When the Mohs hardness of the second metal is too high, it may not be easy to process. The second metal is, for example, selected from at least one of titanium (Ti), manganese (Mn), niobium (Nb), tantalum (Ta), iridium (Ir), vanadium (V), rhenium (Re), osmium (Os), tungsten (W), chromium (Cr), boron (B), ruthenium (Ru) and rhodium (Rh). The thickness of the coating may be, for example, 10 nm to 1 μm, 50 nm to 500 nm, 50 nm to 200 nm, or 50 nm to 150 nm.
[0130] [Method for producing lithium metal battery] A method for manufacturing a lithium metal battery includes: preparing a composition for forming a positive electrode electrolyte; preparing a composition for forming a negative electrode electrolyte; applying the composition for forming a negative electrode electrolyte to a lithium metal negative electrode; cross-linking the applied composition for forming a negative electrode electrolyte to prepare a lithium metal negative electrode coated with a negative electrode electrolyte; stacking the lithium metal negative electrode coated with a negative electrode electrolyte, a porous membrane and a positive electrode to prepare an assembly; injecting the composition for forming a positive electrode electrolyte into the assembly; and cross-linking the injected composition for forming a positive electrode electrolyte to prepare a lithium metal battery including a positive electrode electrolyte, wherein the lithium metal battery includes a positive electrode, a negative electrode and an electrolyte disposed between the positive electrode and the negative electrode, the positive electrode electrolyte includes a first polymer electrolyte, and the first polymer electrolyte includes a first polymer, and the first polymer includes a first repeating unit derived from a first single ion conductive monomer and a second repeating unit derived from a first cross-linking monomer having multiple reactive functional groups. In the lithium metal battery manufactured by the method, the electrolyte includes a positive electrode electrolyte adjacent to the positive electrode and a negative electrode electrolyte adjacent to the negative electrode, thereby preventing degradation of the electrolyte at the high voltage positive electrode and preventing growth of lithium dendrites on the surface of the negative electrode. As a result, degradation of the lithium metal battery is prevented and the cycle characteristics of the lithium metal battery are improved.
[0131] A composition for forming a positive electrode electrolyte is prepared. The composition for forming a positive electrode electrolyte includes a first single ion conductive monomer, a first cross-linking monomer, a thermal initiator and a liquid electrolyte. The content of the first single ion conductive monomer can be 1wt% to 20wt% of the total weight of the composition for forming a positive electrode electrolyte. The content of the first cross-linking monomer can be 1wt% to 20wt% of the total weight of the composition for forming a positive electrode electrolyte. The thermal initiator is tert-amyl peroxide or azo dithermal initiator, but is not limited thereto, and any thermal initiator used in the relevant technical field can be used. The types of the first single ion conductive monomer, the second cross-linking monomer and the liquid electrolyte refer to the above-mentioned positive electrode electrolyte. For example, a composition for forming a positive electrode electrolyte is prepared by adding the first single ion conductive monomer, the first cross-linking monomer and the thermal initiator to the liquid electrolyte.
[0132] A composition for forming a negative electrode electrolyte is prepared. The composition for forming a negative electrode electrolyte includes a second single ion conductive monomer, a second cross-linked monomer, a third polymer, a second inorganic solid electrolyte, a second filler, a second lithium salt, a thermal initiator and a solvent. The content of the second single ion conductive monomer can be 1wt% to 20wt% of the total weight of the composition for forming a negative electrode electrolyte. The content of the second cross-linked monomer can be 1wt% to 20wt% of the total weight of the composition for forming a negative electrode electrolyte. The content of the third polymer can be 1wt% to 40wt% of the total weight of the composition for forming a negative electrode electrolyte. The content of the second inorganic solid electrolyte can be 5wt% to 60wt% of the total weight of the composition for forming a negative electrode electrolyte. The content of the second filler can be 5wt% to 15wt% of the total weight of the composition for forming a negative electrode electrolyte. The content of the second lithium salt can be 1wt% to 30wt% of the total weight of the composition for forming a negative electrode electrolyte. The thermal initiator is tert-amyl peroxide or azo dithermal initiator, but is not limited thereto, and any thermal initiator used in the relevant technical field can be used. The types of the second single ion conductive monomer, the second cross-linked monomer, the third polymer, the second inorganic solid electrolyte, the second filler, the second lithium salt and the solvent refer to the above-mentioned negative electrode electrolyte. For example, a composition for forming a negative electrode electrolyte is prepared by adding a second single ion conductive monomer, a second cross-linked monomer, a third polymer, a second inorganic solid electrolyte, a second filler, a second lithium salt and a thermal initiator to an organic solvent. The organic solvent includes but is not limited to tetrahydrofuran, N-methylpyrrolidone, etc., and any solvent used in the relevant technical field can be used. In the composition for forming a negative electrode electrolyte, the content of the second single ion conductive monomer, the second cross-linked monomer, the third polymer, the second inorganic solid electrolyte, the second filler and the second lithium salt is based on the solid content excluding the solvent.
[0133] A negative electrode in which lithium metal or lithium alloy is disposed on a negative electrode current collector is prepared. A composition for forming a negative electrode electrolyte is applied to the lithium metal negative electrode. The coating method is not particularly limited and includes a rod coating method, a spin coating method, and the like. The coating can be performed, for example, by using a scraper.
[0134] The composition for forming the negative electrode electrolyte is crosslinked to prepare a lithium metal negative electrode coated with the negative electrode electrolyte. The crosslinking is, for example, thermal crosslinking, ultraviolet crosslinking, etc. The thermal crosslinking can be performed, for example, at a temperature of 60° C. to 80° C. for 1 to 2 hours, but is not limited to these conditions and can be appropriately selected according to the desired degree of crosslinking.
[0135] Prepare a positive electrode. For example, a positive electrode active material composition is prepared by mixing a positive electrode active material, a conductive material, a binder and a solvent. The prepared positive electrode active material composition is directly applied to a positive electrode current collector and dried to produce a positive electrode plate having a positive electrode active material layer formed thereon. Alternatively, the positive electrode active material composition is cast on a separate support, peeled off from the support to obtain a film, and then the obtained film is laminated onto a positive electrode current collector to produce a positive electrode plate having a positive electrode active material layer formed thereon. The solvent is not particularly limited, such as N-methylpyrrolidone. It is also possible to form pores inside the electrode plate by further adding a plasticizer or a pore former to the positive electrode active material composition. The positive electrode can be manufactured by the above method, but the present disclosure is not necessarily limited to the method. The type and content of the positive electrode active material, the conductive material and the binder refer to the above-mentioned positive electrode active material layer.
[0136] The lithium metal negative electrode coated with the negative electrode electrolyte, the porous membrane and the positive electrode are stacked to prepare an assembly. The assembly is housed in a can or a bag. The porous membrane refers to the above-mentioned porous support.
[0137] The positive electrode electrolyte forming composition is injected into the assembly. The positive electrode electrolyte forming composition is injected into the assembly accommodated in the can or bag, thereby impregnating the positive electrode electrolyte forming composition into the porous film and the positive electrode active material layer.
[0138] The injected composition for forming a positive electrode electrolyte is cross-linked to manufacture a lithium metal battery including a positive electrode electrolyte. Cross-linking is, for example, thermal cross-linking, ultraviolet cross-linking, etc. Thermal cross-linking can be performed, for example, at a temperature of 60°C to 80°C for 1 to 2 hours, but is not limited to these conditions and can be appropriately selected according to the desired degree of cross-linking. As the composition for forming a positive electrode electrolyte is cross-linked, a positive electrode electrolyte is formed in an area where a porous film and a positive electrode active material layer are arranged. The positive electrode electrolyte is disposed in the pores included in the positive electrode active material layer and in the pores included in the porous film.
[0139] The manufactured lithium metal battery can have the attached Figures 6 to 8 structure.
[0140] Reference Figure 6 , the lithium metal battery 1 according to the embodiment includes a positive electrode 3, the above-mentioned negative electrode 2 and a separator 4. The positive electrode 3, the negative electrode 2 and the separator 4 are wound or folded to form a battery structure 7. The formed battery structure 7 is accommodated in a battery case 5. A composition for forming a positive electrode electrolyte is injected into the battery case 5, cross-linked, and sealed with a cap assembly 6, thereby completing the lithium metal battery 1. The battery case 5 is cylindrical, but is not necessarily limited to this shape, and is, for example, rectangular, thin-film, etc.
[0141] Reference Figure 7, the lithium metal battery 1 according to the embodiment includes a positive electrode 3, the above-mentioned negative electrode 2 and a separator 4. The separator 4 is placed between the positive electrode 3 and the negative electrode 2, and the positive electrode 3, the negative electrode 2 and the separator 4 are wound or folded to form a battery structure 7. The formed battery structure 7 is accommodated in a battery case 5. The lithium metal battery 1 may include an electrode terminal 8 serving as an electrical path for inducing the current formed in the battery structure 7 to the outside. The composition for forming a positive electrode electrolyte is injected into the battery case 5, cross-linked and sealed, thereby completing the lithium metal battery 1. The battery case 5 is cylindrical, but is not necessarily limited to this shape, and is, for example, rectangular, thin film, etc.
[0142] Reference Figure 8 , the lithium metal battery 1 according to the embodiment includes a positive electrode 3, the above-mentioned negative electrode 2 and a separator 4. The separator 4 is placed between the positive electrode 3 and the negative electrode 2 to form a battery structure 7. The battery structure 7 is stacked in a double battery structure and then housed in a battery case 5. The lithium metal battery 1 may include an electrode tab 8 serving as an electrical path for inducing the current formed in the battery structure 7 to the outside. A composition for forming a positive electrode electrolyte is injected into the battery case 5, cross-linked and sealed, thereby completing the lithium metal battery 1. The battery case 5 is cylindrical, but is not necessarily limited to this shape, and is, for example, rectangular, thin film, etc.
[0143] Pouch-type lithium metal batteries use pouches as Figures 6 to 8 A housing for a lithium metal battery. A pouch-type lithium metal battery may include at least one battery structure. A separator is placed between a positive electrode and a negative electrode to form a battery structure. A plurality of battery structures are laminated in the thickness direction, then impregnated with an organic electrolyte, and contained and sealed in a bag to complete a pouch-type lithium metal battery. For example, although not shown in the accompanying drawings, the above-mentioned positive electrode, negative electrode, and separator may be simply laminated and contained in a bag in the form of an electrode assembly, or may be wound or folded into a core-shaped electrode assembly and then contained in a bag. Subsequently, a composition for forming a positive electrode electrolyte is injected into the bag, thermally cross-linked, and sealed to complete the lithium metal battery.
[0144] Since the lithium metal battery of the present disclosure has excellent discharge capacity, life characteristics and high energy density, it is used, for example, in electric vehicles (EVs). For example, lithium metal batteries are used in hybrid vehicles such as plug-in hybrid electric vehicles (PHEVs). Lithium metal batteries are also used in fields that require large amounts of power storage. For example, lithium metal batteries are used in electric bicycles, power tools, etc.
[0145] A plurality of lithium metal batteries are stacked to form a battery module, and a plurality of battery modules form a battery pack. The battery pack can be used in any device requiring high capacity and high output. For example, the battery pack can be used in a notebook computer, a smart phone, an electric vehicle, etc. The battery module includes, for example, a plurality of batteries and a frame for holding these batteries. The battery pack includes, for example, a plurality of battery modules and bus bars connecting these battery modules. The battery module and / or the battery pack may also include a cooling device. The plurality of battery packs are controlled by a battery management system. The battery management system includes a battery pack and a battery control device connected to the battery pack.
[0146] The inventive concept will be described in more detail through the following examples and comparative examples. However, these examples are intended to illustrate the inventive concept, and the scope of the inventive concept is not limited thereto.
[0147] (Composition for forming positive electrode electrolyte and positive electrode electrolyte)
[0148] Preparation Example 1: MTFSILi + ester crosslinker (PETTA) + liquid electrolyte 0.6 M LiBF4 and 0.6 M lithium difluoro(oxalato)borate (LiDFOB) were added to a mixed solvent of diethyl carbonate (DEC) and fluoroethylene carbonate (FEC) (volume ratio of 2:1) to prepare a liquid electrolyte.
[0149] Lithium methacrylic acid sulfonyl (trifluoromethanesulfonyl) imide (MTFSILi) represented by the following Formula 1 as a first single ion conductive monomer, pentaerythritol tetraacrylate (PETTA) represented by the following Formula 2 as a first cross-linking monomer, and tert-amyl peroxide as a thermal initiator were added to a liquid electrolyte to prepare a composition for forming a positive electrode electrolyte.
[0150] <Formula 1> <Formula 2> In the composition for forming a positive electrode electrolyte, the content of MTFSILi is 2.8 wt %, the content of PETTA is 2 wt %, and the content of tert-amyl peroxide is 0.02 wt % relative to the total weight of the composition for forming a positive electrode electrolyte.
[0151] The prepared composition for forming a positive electrode electrolyte was impregnated into a porous polyethylene film and then cross-linked in an oven at 70° C. for 1 hour and 30 minutes to prepare a positive electrode electrolyte.
[0152] Comparative preparation example 1: MTFSILi + diol crosslinker (ETPTA) + liquid electrolyte A composition for forming a positive electrode electrolyte was prepared in the same manner as in Preparation Example 1, except that 3 wt % of ethoxylated trimethylolpropane triacrylate (ETPTA) represented by the following Formula 3 was used as a diol-based crosslinking agent instead of 2 wt % of PETTA as a first crosslinking monomer: <Formula 3> Here, in Formula 3, n is 2 to 100.
[0153] The prepared composition for forming a positive electrode electrolyte was impregnated into a porous polyethylene film and then cross-linked in an oven at 70° C. for 1 hour and 30 minutes to prepare a positive electrode electrolyte.
[0154] Comparative preparation example 2: ester crosslinker (PETTA) + liquid electrolyte A composition for forming a positive electrode electrolyte was prepared in the same manner as in Preparation Example 1, except that the first single ion conductive monomer was not added.
[0155] The prepared composition for forming a positive electrode electrolyte was impregnated into a porous polyethylene film and then cross-linked in an oven at 70° C. for 1 hour and 30 minutes to prepare a positive electrode electrolyte.
[0156] (Composition for forming negative electrode electrolyte and negative electrode)
[0157] Preparation Example 2: Lithium Metal Anode Coated with Anode Electrolyte 6 parts by weight of styrene (trifluoromethane) sulfonyl imide lithium (STFSLi) represented by the following formula 4 as a second single ion conductive monomer, 10 parts by weight of divinylbenzene (DVB) as a second crosslinking monomer, 25 parts by weight of lithium lanthanum zirconium oxide (LLZO, Li7La3Zr1.4Zr0.6O 12 ), 5 parts by weight of reactive alumina as a second filler, 36 parts by weight of poly(ethylene oxide) (PEO) as a third polymer, 18 parts by weight of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) as a second lithium salt, and 0.1 parts by weight of an azo type II thermal initiator (e.g., 2,2'-azobisisobutyronitrile) as a thermal initiator are added to a tetrahydrofuran (THF) solvent to prepare a composition for forming a negative electrode electrolyte.
[0158] <Formula 4> A negative electrode having a lithium metal film with a thickness of 20 μm provided on a negative electrode current collector was prepared. A copper foil with a thickness of 9 μm was used as the negative electrode current collector.
[0159] The composition for forming a negative electrode electrolyte prepared in Preparation Example 2 was applied to the lithium metal of the negative electrode using a scraper, and dried and thermally cross-linked in a vacuum oven at 70°C for 9 hours to prepare a negative electrode having a negative electrode current collector / lithium metal / negative electrode electrolyte layer structure.
[0160] The negative electrode electrolyte is a gel polymer electrolyte and the thickness of the negative electrode electrolyte layer is about 10 μm.
[0161] A scanning electron microscope image of the surface of the lithium metal negative electrode coated with the negative electrode electrolyte prepared in Preparation Example 2 is shown in Figure 2a In. Figure 2a As shown in , it was confirmed that the negative electrode electrolyte was uniformly coated on the surface of lithium metal. It was shown that the negative electrode electrolyte had a composition in which inorganic solid electrolyte particles and an organic polymer were mixed.
[0162] Comparative preparation example 3: lithium metal anode The same negative electrode was used in which a lithium metal film having a thickness of 20 μm was provided on the negative electrode current collector used previously.
[0163] The scanning electron microscope image of the surface of the lithium metal negative electrode prepared in the comparative preparation example 3 is shown in Figure 2b In. Figure 2b As shown in , the surface of lithium metal is flat.
[0164] (Lithium Metal Batteries)
[0165] Example 1: Positive Electrolyte + Negative Electrolyte
[0166] (Preparation of negative electrode) The lithium metal negative electrode coated with the negative electrode electrolyte prepared in Preparation Example 2 was prepared.
[0167] (Preparation of positive electrode) LiCoO2 powder and a carbon conductive material (conductive carbon black (Super P), Timcal Co., Ltd.) were mixed in a weight ratio of 90:5, and then a polyvinylidene fluoride (PVDF) binder solution was added to the mixture to prepare a positive electrode active material slurry in which the weight ratio of active material:carbon conductive material:binder was 90:5:5.
[0168] The prepared slurry was applied onto an aluminum substrate having a thickness of 20 μm using a doctor blade, dried at 120° C. under reduced pressure, and then rolled using a roll press to prepare a positive electrode in the form of a sheet. The thickness of the positive electrode active material layer was 80 μm.
[0169] (Manufacturing of lithium metal batteries) A polyethylene separator was placed between the prepared positive electrode and negative electrode to prepare a laminate. The composition for forming a positive electrode electrolyte prepared in Preparation Example 1 was injected into the prepared laminate, and then thermally cross-linked in an oven at 70° C. for 1 hour and 30 minutes to manufacture a lithium metal battery including a positive electrode electrolyte. The positive electrode electrolyte was a gel polymer electrolyte.
[0170] Lithium metal batteries have a positive electrode / positive electrode electrolyte (separator) / negative electrode electrolyte / lithium metal negative electrode structure.
[0171] Comparative Example 1: Positive Electrolyte Only A lithium metal battery was manufactured in the same manner as in Example 1, except that the lithium metal anode prepared in Comparative Preparation Example 3 was used instead of the lithium metal anode coated with the anode electrolyte prepared in Preparation Example 2.
[0172] Comparative Example 2: Negative Electrolyte Only A lithium metal battery was manufactured in the same manner as in Example 1, except that a liquid electrolyte was injected instead of the composition for forming a positive electrode electrolyte prepared in Preparation Example 1 and the thermal cross-linking process was omitted.
[0173] A liquid electrolyte was used in which 0.6 M LiBF4 and 0.6 M LiDFOB were added to a mixed solvent of DEC and FEC in a volume ratio of 2:1.
[0174] Evaluation Example 1: Evaluation of electrochemical stability of positive electrode electrolyte The positive electrode electrolytes prepared in Preparation Example 1 and Comparative Preparation Example 1 were prepared respectively.
[0175] A lithium metal negative electrode was used as a reference electrode, and the prepared positive electrode electrolyte was placed between the reference electrode and the working electrode, and the electrolyte was cross-linked to prepare a test cell. A SUS current collector was used as a working electrode.
[0176] The current density of lithium metal versus voltage (up to 6.0 V) was measured using linear sweep voltammetry at a scan rate of 1 mV / s, and the measurement results are shown in Figure 3 middle.
[0177] like Figure 3 As shown in FIG. 1 , the positive electrode electrolyte of Preparation Example 1 has a voltage of 0.003 mA / cm2 at 5.0 V compared to lithium metal due to side reactions such as oxidation. 2 or lower current density, which is very low. In contrast, the positive electrolyte of Comparative Preparation Example 1 has a current density of 0.005 mA / cm 2 or higher current density.
[0178] Therefore, it was confirmed that the cathode electrolyte of Preparation Example 1 had improved electrochemical stability at a high voltage of up to 5.5 V compared to the cathode electrolyte of Comparative Preparation Example 1.
[0179] Evaluation Example 2: Measurement of ionic conductivity of positive electrode electrolyte For the positive electrode electrolytes prepared in Preparation Example 1 and Comparative Preparation Example 2, the ionic conductivity (σ) and the lithium ion migration number (t+) were measured at 25°C using a lithium symmetric cell and an impedance analyzer (Solartron 1260A impedance / gain phase analyzer combined with a Solartron 1287 electrochemical interface). The ionic conductivity and the lithium ion migration number were derived using an alternating current (AC) impedance method combined with a steady-state current method. First, the initial lithium interface resistance (Ro) was measured by impedance spectroscopy in the frequency range of 0.1 Hz to 100 kHz, and then a small direct current (DC) voltage (<30 mV) was applied until a steady-state current (Iss) was obtained (time = 3000 s), and finally the steady-state lithium interface resistance (Rss) was measured by impedance spectroscopy in the frequency range of 0.1 Hz to 100 kHz. The lithium ion migration number (t+) and the lithium ion conductivity (σ(Li + )).
[0180] The lithium symmetric battery has a Li / negative electrolyte / Li structure by placing a positive electrolyte membrane between lithium electrodes, and the structure is sealed within the battery. The measurement results of the lithium symmetric battery are shown in Table 1 below.
[0181] [Table 1]
[0182] As shown in Table 1, compared with the positive electrode electrolyte of Comparative Preparation Example 2, the positive electrode electrolyte of Preparation Example 1 has improved ion conductivity, lithium ion transference number, and lithium ion conductivity.
[0183] In the positive electrode electrolyte of Preparation Example 1, since anions are fixed on the backbone derived from the first single ion conductive monomer, only lithium ions move. Therefore, compared with the positive electrode electrolyte of Comparative Preparation Example 2, the ion conductivity, lithium ion transference number, and lithium ion conductivity of the positive electrode electrolyte of Preparation Example 1 are increased, respectively.
[0184] Evaluation Example 3: Charge-discharge test of a lithium battery including a positive electrode electrolyte A positive electrode was prepared in the same manner as in Example 1. The lithium metal negative electrode prepared in Comparative Preparation Example 3 was prepared as a negative electrode. A polyethylene separator was placed between the prepared positive electrode and the negative electrode to prepare a laminate.
[0185] The composition for forming a positive electrode electrolyte prepared in Preparation Example 1 was injected into the laminate, and then thermally cross-linked in an oven at 70° C. for 1 hour and 30 minutes to manufacture a lithium metal battery including the positive electrode electrolyte.
[0186] Then, the positive electrode electrolyte forming composition prepared in Comparative Preparation Example 1 was injected into the laminate, and then thermally cross-linked in an oven at 70° C. for 1 hour and 30 minutes to separately manufacture a lithium metal battery including the positive electrode electrolyte of Comparative Preparation Example 1.
[0187] The lithium battery including the positive electrode electrolyte of Preparation Example 1 and the lithium battery including the positive electrode electrolyte of Comparative Preparation Example 1 were charged at a constant current of 0.2C rate at 25°C until the voltage reached 4.48V (relative to Li). Subsequently, the lithium metal battery was discharged at a constant current of 0.5C rate until the voltage reached 3.0V (relative to Li) during discharge. This charge-discharge cycle was repeated 100 times.
[0188] In each charge-discharge cycle, a pause of 5 minutes was allowed after each charge / discharge cycle. The results of the charge / discharge experiment at room temperature are shown in Table 2 below. The capacity retention ratio is defined by Equation 1 below.
[0189] <Equation 1> Capacity retention rate [%] = [discharge capacity at the 100th cycle / discharge capacity at the 1st cycle] × 100 [Table 2]
[0190] As shown in Table 2, the lithium battery including the positive electrode electrolyte of Preparation Example 1 exhibited significantly improved initial discharge capacity and lifespan characteristics compared to the lithium battery including the positive electrode electrolyte of Comparative Preparation Example 1.
[0191] It is confirmed that these results are because the electrochemical stability of the positive electrode electrolyte of Preparation Example 1 is improved compared with that of Comparative Preparation Example 1, thereby suppressing side reactions such as decomposition due to oxidation of the positive electrode electrolyte during charge and discharge.
[0192] Evaluation Example 4: Confirmation of the cross-sectional structure of a lithium battery including a negative electrode electrolyte A positive electrode was prepared in the same manner as in Example 1. A negative electrode coated with a negative electrode electrolyte layer was prepared in the same manner as in Example 2. A polyethylene separator was placed between the prepared positive electrode and the negative electrode to prepare a laminate. The composition for forming a positive electrode electrolyte prepared in Example 1 was injected into the laminate and the laminate was sealed, and then the composition was thermally cross-linked in an oven at 70°C for 1 hour and 30 minutes to manufacture a lithium metal battery including a positive electrode electrolyte and a negative electrode electrolyte of Example 1. The lithium battery including a positive electrode electrolyte and a negative electrode electrolyte of Example 1 was charged at a constant current at 25°C and then disassembled. A scanning electron microscope image of a cross section of the negative electrode was measured, and the results are shown in Figure 4 middle.
[0193] like Figure 4 As shown in , it was confirmed that a lithium metal layer having a thickness of about 20 μm was additionally placed between the negative electrode electrolyte layer and the lithium metal negative electrode.
[0194] Therefore, it was confirmed that the negative electrode electrolyte layer suppressed the side reaction between the liquid electrolyte and the lithium metal by blocking the direct contact between the liquid electrolyte and the lithium metal layer.
[0195] Evaluation Example 5: Room Temperature Charge-Discharge Test The lithium batteries manufactured in Example 1 and Comparative Examples 1 and 2 were charged at a constant current of 0.2C rate at 25°C until the voltage reached 4.48V (relative to Li). Subsequently, the lithium batteries were discharged at a constant current of 0.5C rate until the voltage reached 3.0V (relative to Li) during discharge.
[0196] This cycle was repeated 500 times under the same conditions. In each charge-discharge cycle, a pause of 5 minutes was allowed after each charge / discharge cycle.
[0197] Some results of the room temperature charge-discharge experiments are shown in Tables 3 and Figure 5 The capacity retention rate is defined by the following equation 2.
[0198] <Equation 2> Capacity retention rate [%] = [discharge capacity at the 500th cycle / discharge capacity at the 1st cycle] × 100 [Table 3]
[0199] like Figure 5 As shown in Table 3, the lithium metal battery of Example 1 has an improved capacity retention ratio compared to the lithium metal batteries of Comparative Examples 1 and 2.
[0200] It was confirmed that the lithium metal battery of Example 1 suppressed side reactions and improved reversibility of electrode reactions by simultaneously including a positive electrode electrolyte having excellent high voltage stability and excellent lithium ion conductivity and a negative electrode electrolyte suppressing lithium dendrite formation.
[0201] Although the exemplary embodiments have been described in detail with reference to the accompanying drawings, the inventive concept is not limited to these exemplary embodiments. Obviously, a person skilled in the art to which the inventive concept belongs can derive various examples of changes or modifications within the scope of the technical ideas described in the claims, and these examples naturally fall within the technical scope of the inventive concept.
[0202] [Explanation of Reference Numerals] 1: Lithium battery 2, 20: negative electrode 3, 10: positive electrode 4: Diaphragm 5: Battery housing 6: Cover assembly 7: Battery structure 8: Electrode terminal block 11: Positive electrode current collector 12: Positive electrode active material layer 21: Negative electrode current collector 22: Negative electrode active material layer 30: Electrolytes 30a: Positive Electrolyte 30b: Negative electrolyte.
[0203] Industrial Applicability According to a lithium metal battery including an electrolyte having a novel structure, it is possible to provide a lithium metal battery that prevents degradation of a positive electrode electrolyte, prevents side reactions of a lithium metal negative electrode, and improves cycle characteristics.
Claims
1. A lithium metal battery, comprising: positive electrode; negative electrode; as well as an electrolyte disposed between the positive electrode and the negative electrode, Wherein, the negative electrode comprises lithium metal, The electrolyte includes a positive electrode electrolyte disposed adjacent to the positive electrode and a negative electrode electrolyte disposed between the positive electrode electrolyte and the negative electrode. The positive electrode electrolyte includes a first polymer electrolyte, the first polymer electrolyte includes a first polymer, and The first polymer includes a first repeating unit derived from a first single ion conductive monomer and a second repeating unit derived from a first cross-linking monomer having a plurality of reactive functional groups.
2. The lithium metal battery according to claim 1, wherein The first single ion conducting monomer comprises a reactive functional group, an anion functional group and a counter cation, The reactive functional group includes vinyl, acrylic, methacrylic, (4-vinyl)phenyl or a combination thereof. The anionic functional group includes a carboxyl group, a sulfonic acid group, a sulfonimide group or a combination thereof, and The counter cation is an alkali metal cation.
3. The lithium metal battery according to claim 1, wherein The first cross-linking monomer includes three or more reactive functional groups.
4. The lithium metal battery according to claim 1, wherein The first crosslinking monomer is a monomer that does not contain an alkylene oxide repeating unit, and The first cross-linking monomer includes polycaprolactone diacrylate, polycaprolactone dimethacrylate, pentaerythritol tetraacrylate, pentaerythritol tetramethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate or a combination thereof.
5. The lithium metal battery according to claim 1, wherein The first polymer may be present in an amount of 0.2 wt % to 10 wt % relative to the total weight of the first polymer electrolyte.
6. The lithium metal battery according to claim 1, wherein The first polymer electrolyte further includes at least one selected from a first inorganic solid electrolyte, a first filler, a first organic solvent, and a first lithium salt.
7. The lithium metal battery according to claim 6, wherein: The first organic solvent comprises a carbonate organic solvent, and The carbonate organic solvent includes ethylene carbonate, propylene carbonate, fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate or a combination thereof.
8. The lithium metal battery according to claim 6, wherein The first lithium salt includes LiBF4, LiPF6, LiClO4, LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiC(CF2SO2)3, LiBF2(C2O4) or a combination thereof.
9. The lithium metal battery according to claim 1, wherein The positive electrode electrolyte does not contain a compound including an alkylene oxide repeating unit, The compound comprising the alkylene oxide repeating unit is a monomer, an oligomer, a polymer or a combination thereof, and The alkylene oxide group is an ethylene oxide group.
10. The lithium metal battery according to claim 1, wherein The current density of the cathode electrolyte at 5.0 V versus lithium metal was 0.003 mA / cm2 as measured by linear sweep voltammetry (LSV) at a scan rate of 1 mV / s. 2 or smaller.
11. The lithium metal battery according to claim 1, wherein The positive electrode electrolyte has a lithium ion transference number of 0.3 or more.
12. The lithium metal battery according to claim 1, further comprising a porous support disposed between the positive electrode and the negative electrode, in, The positive electrode electrolyte is impregnated into the porous support.
13. The lithium metal battery according to claim 1, wherein The negative electrode electrolyte includes a second polymer electrolyte, the second polymer electrolyte includes a second polymer, and The second polymer includes a third repeating unit derived from a second single ion conductive monomer and a fourth repeating unit derived from a second cross-linking monomer having a plurality of reactive functional groups.
14. The lithium metal battery according to claim 13, wherein The second crosslinking monomer includes an aromatic ring, and The second cross-linking monomer may be present in an amount of 2 wt % to 10 wt % relative to the total weight of the second polymer electrolyte.
15. The lithium metal battery according to claim 13, wherein The second polymer electrolyte further comprises at least one selected from a second inorganic solid electrolyte, a second filler, a second lithium salt and a third polymer, The second inorganic solid electrolyte comprises an oxide solid electrolyte, the particle size of the oxide solid electrolyte is 400 nm to 800 nm, and the content of the second inorganic solid electrolyte is 5 wt % to 60 wt % relative to the total weight of the second polymer electrolyte, and The second filler includes inorganic particles, the inorganic particles include metal oxide, the particle size of the metal oxide is 20 nm to 400 nm, and the content of the second filler is 5 wt % to 15 wt % relative to the total weight of the second polymer electrolyte.
16. The lithium metal battery according to claim 15, wherein The second polymer electrolyte includes the second filler and the second polymer, and The second filler is chemically bonded to the second polymer through a reactive functional group disposed on a surface of the second filler.
17. The lithium metal battery according to claim 15, wherein The third polymer is an ion conducting polymer, and the third polymer includes alkylene oxide repeating units.
18. The lithium metal battery according to claim 1, wherein Each of the positive electrode electrolyte and the negative electrode electrolyte is a polymer gel electrolyte, and The elastic modulus of the negative electrode electrolyte is greater than the elastic modulus of the positive electrode electrolyte.
19. The lithium metal battery according to claim 1, wherein The thickness of the positive electrode electrolyte is greater than the thickness of the negative electrode electrolyte, The thickness of the lithium metal is greater than the thickness of the negative electrode electrolyte, The thickness of the positive electrode electrolyte is 8 μm to 25 μm, The thickness of the lithium metal is 10 μm to 200 μm, and The thickness of the negative electrode electrolyte is 1 μm to 20 μm.
20. A method for manufacturing a lithium metal battery, the method comprising: preparing a composition for forming a positive electrode electrolyte; preparing a composition for forming a negative electrode electrolyte; Applying the composition for forming a negative electrode electrolyte onto a lithium metal negative electrode; cross-linking the applied composition for forming a negative electrode electrolyte to prepare the lithium metal negative electrode coated with the negative electrode electrolyte; stacking the lithium metal negative electrode coated with the negative electrode electrolyte, a porous membrane, and a positive electrode to prepare an assembly; injecting the composition for forming a positive electrode electrolyte into the assembly; and cross-linking the injected composition for forming a positive electrode electrolyte to prepare a lithium metal battery including the positive electrode electrolyte, The lithium metal battery comprises a positive electrode, a negative electrode and an electrolyte disposed between the positive electrode and the negative electrode. The positive electrode electrolyte includes a first polymer electrolyte, and the first polymer electrolyte includes a first polymer, and The first polymer includes a first repeating unit derived from a first single ion conductive monomer and a second repeating unit derived from a first cross-linking monomer having a plurality of reactive functional groups.